WC is better than BMI as a predictor of diabetes and pre diabetes in Hindu priests of India - Sharma, Booloo; Sarmah, Devajit (Asian Journal of Medical Sciences, 2014)
Background & Objective: Over a period of time great emphasis has been made to prevent diabetes and its complications, and BMI have evolved into a reliable indicator for predicting the incidence of diabetes mellitus. But for a common man BMI is difficult to understand and calculate and there is a need for a more easily acceptable, understandable and measurable parameter as a predictor for diabetes risks. WC is one such parameter and the study tries to establish a correlation between (WC) and FBS with an aim to establish WC as a predictor of diabetes risks. Methods: From our ongoing diabetes screening study 220 Hindu priests were selected. This includes 55 newly diagnosed diabetes, 55 newly diagnosed pre-diabetes and 110 age matched controls. BMI, WC and FBS were calculated. A statistical correlation was established between BMI and FBS and between WC and FBS. The upper limit above which the risk association became statistically significant (P < 0.005) with pre-diabetes and diabetes were considered to be the cutoff for normal values. Results & Conclusion: The WC was 31.77 ± 2.63, 35.82 ± 1.04 and 41.07 ± 2.24 inches in controls, pre-diabetes and diabetes respectively. A statistically significant difference (P < 0.005) for WC was found between controls and pre-diabetes and diabetes. Normal cut off for waist circumference among the Hindu priest is <35 inches or <90 centimeters. Also, statistically significant correlation was established between BMI and FBS and between WC and FBS however, correlation between WC and FBS is better than the former. WC more or less correlates with the pant/pyjama/trouser size, and almost everybody is aware of their pant size. Since WC is a more understandable term for the layman and which can be measured and tracked by the layman themselves, WC could be used as a better and more beneficial predictor of diabetes risk. Simply monitoring the pant size can make the layman understand when to ring the alarm and take medical attention or modify lifestyles. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10097 Asian Journal of Medical Sciences Vol.6(1) 2015 91-94